High Density Lipoproteins: Metabolism, Function, and Therapeutic Potential - Jomard, Anne; Osto, Elena (Frontiers in Cardiovascular Medicine, 2020)
High Density Lipoproteins (HDL) has long been considered as “good cholesterol”, beneficial to the whole body and, in particular, to cardio-vascular health. However, HDL is a complex particle that undergoes dynamic remodeling through interactions with various enzymes and tissues throughout its life cycle, making the complete understanding of its functions and roles more complicated than initially expected. In this review, we explore the novel understanding of HDL behavior in health and disease as a multifaceted class of lipoprotein, with different size subclasses, molecular composition, receptor interactions, and functionality. Further, we report on emergent HDL based therapeutics tested in small and larger scale clinical trials and their mixed successes.